Presentation zen : simple ideas on presentation design and delivery - Reynolds, Garr (New Riders, 2008)
Publikace přináší návod, jak vytvářet prezentace v Microsoft PowerPoint
Obsahuje rejstřík
Keywords: prezentace informací; prezentační grafika; Microsoft PowerPoint (software); presentation of information; presentation graphics; Microsoft PowerPoint; příručky; handbooks,manuals, etc